PELATIHAN SERTIFIKASI HALAL SEBAGAI UPAYA PENGEMBANGAN UMKM DI DESA TEPIAN MAKMUR - Akmaluddin, Akmaluddin; Ahmadin, Maizir; Ulfah, Ulfah; Dewi, Rita Sri; Yanda, Nurisa Putri; Lestari, Eka (El-Madaniyah : Jurnal Pengabdian Masyarakat, 2024)
The aim of this PkM is to provide additional insight to MSMEs in Tepian Makmur Village about the importance of halal certification, and to assist MSMEs in expanding the marketing of their products in order to increase sales and income. The PkM method uses the Community Based Research method, namely the resource person's explanation to partners. The method used in this activity is a meeting or face-to-face meeting between the resource person and the partner. The results of implementing PkM are: making Business Identification Numbers and certificate labels on MSME products as well as making new innovative products